Reprimarization in Latin America?: Effects of chinese demand on the latin american export pattern and the intern economic structures (1995-2016) - Santana Suárez, Néstor (Papeles de Europa, 2019)
The purpose of this research is to study if the Chinese demand, considering its own characteristics, is stimulating a dynamic of reprimarization of Latin America in the period 1995-2016. In order to do this, we analyze the export pattern of Argentina, Brazil, Chile, Cuba, Peru, Uruguay and Venezuela focusing on primary products and manufactures based on natural resources. We distinguish trade with China and the rest of the world, and then we study the consequences of the change in the export pattern on national economic structures. The main conclusions of the research are that, although for all the countries studied, we can appreciate a process of reprimarization of their exports; only Brazil and Peru present evidence of a recent reprimarising dynamic of their internal structure, which is still very short-termed.